1999
DOI: 10.1177/0265407599166010
|View full text |Cite
|
Sign up to set email alerts
|

Unrealistic Gendered and Relationship-Specific Beliefs: Contributions to Investments and Commitment in Dating Relationships

Abstract: This study focuses on beliefs about intimate relationships, and how these beliefs are related to individuals' experiences in ongoing romantic relationships. More specifically, we examined how unrealistic beliefs contributed to commitment and components of the investment model (rewards, costs, match to ideal comparison level, alternatives, investment size, barriers). Two types of beliefs were examined: unrealistic gendered beliefs focused on assumptions about irreconcilable differences in men and women's relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 31 publications
0
15
0
1
Order By: Relevance
“…Podczas procesu wychowania dziewczynki uczone są interpersonalnych umiejętności oraz wyższości takich uczuć, jak: przywiązanie, bliskość, empatia, troska, odpowiedzialność za związki interpersonalne (Jacoby 1995, za: Brannon 2002, Mandal 2004. Konsekwencją zróżnicowanej ze względu na płeć socjalizacji jest uczenie dziewcząt przejmowania odpowiedzialności za relacje (związki) i pełnienie w nich funkcji opiekunek (Fitzpatrick, Sollie 1999). Mężczyźni postrzegają sytuacje związane z bliskością w kategoriach zagrożenia ich władzy oraz słabości (Mandal 2004).…”
Section: Interpretacja Wynikówunclassified
“…Podczas procesu wychowania dziewczynki uczone są interpersonalnych umiejętności oraz wyższości takich uczuć, jak: przywiązanie, bliskość, empatia, troska, odpowiedzialność za związki interpersonalne (Jacoby 1995, za: Brannon 2002, Mandal 2004. Konsekwencją zróżnicowanej ze względu na płeć socjalizacji jest uczenie dziewcząt przejmowania odpowiedzialności za relacje (związki) i pełnienie w nich funkcji opiekunek (Fitzpatrick, Sollie 1999). Mężczyźni postrzegają sytuacje związane z bliskością w kategoriach zagrożenia ich władzy oraz słabości (Mandal 2004).…”
Section: Interpretacja Wynikówunclassified
“…To explain, there are some study findings yielding that women were more committed than men in dating relationships (Fitzpatrick & Sollie, 1999). It was reported that women were higher in investments.…”
Section: Predictors Of Commitment In the Literaturementioning
confidence: 99%
“…Though research on gender differences shows that the differences in communicative behaviors between men and women tend to be small and that there are often more differences within sexes than between them (see Dindia & Canary, 2006), disclosure and social support are two areas where communicative differences between men and women exist and are meaningful (Burleson et al, 2009;Dindia & Allen, 1992). Because women, on average, are socialized to be relationship oriented, they may be better at detecting problems in their relationships than men (Fitzpatrick & Sollie, 1999). Given that openness is often equated with healthy relationships in the United States (Petronio, 2000), people are likely to associate their own and their partner's avoidance with potential problems (Bochner, 1982;Parks, 1982) and become dissatisfied as a result.…”
Section: The Association Between Topic Avoidance and Relational Dissamentioning
confidence: 99%